2004
DOI: 10.1002/bit.20132
|View full text |Cite
|
Sign up to set email alerts
|

Reduced protein adsorption at solid interfaces by sugar excipients

Abstract: Sugar excipients are shown to reduce the adsorption of ribonuclease A, bovine serum albumin, and hen egg white lysozyme at the liquid-solid interface. The amount of protein adsorbed decreased as the concentration of the sugar increased. At the same sugar concentration, the ability of sugars to reduce protein adsorption followed the trend: trisaccharides > disaccharides > 6-carbon polyols > monosaccharides. This trend in adsorbed protein amounts among sugars was explained by stabilization of the protein native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…8,26,27,44 Detail osmolyte-protein interaction mechanisms have recently been published in a review by Bolen and Rose. 45 In our case, two independent analyses viz.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,26,27,44 Detail osmolyte-protein interaction mechanisms have recently been published in a review by Bolen and Rose. 45 In our case, two independent analyses viz.…”
Section: Discussionmentioning
confidence: 98%
“…[20][21][22][23][24][25] Sugars have been used to reduce protein adsorption on surfaces, 26 denaturation, 27 and aggregation 28 in aqueous solutions and their inhibitory effect on the denaturation of 'amyloid' proteins has also been reported. 12,13,[29][30][31][32][33] Wendorf et al 8 conducted a systematic study of several different sugars, viz. mono, di, and trisaccharide in order to investigate their efficacy in reducing protein adsorption at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of other classes of additives on damage at the air-water interface is less clear. For example, it is now known that increasing conformational stability can decrease the damage that occurs at an interface (363,364). On the other hand, addition of an excluded solute, like sucrose, increases the surface tension at the air-water interface, which can increase the likelihood of conformational rearrangement.…”
Section: Air-water Interfacementioning
confidence: 98%
“…It has been shown that aqueous solutions of sugars and polyhydric alcohols protect the native conformation of various enzymes and proteins. Stabilization of various enzymes by sugars and polyols has been extensively described (Breccia et al 1999;Bustos et al 1999;Li et al 2000;Saunders et al 2000;Wendorf et al 2004;Domenico et al 2004;Ashie et al 2008;Gangadhara et al 2008;Sukenik and Harries 2009). Since many organisms synthesise certain polyhydric alcohols in response to environmental stress conditions, they have evolutionary signifi cance (Bolen and Baskakov 2001;Bolen 2004).…”
Section: Introductionmentioning
confidence: 99%